Patrimônio afetivo e cultural no contexto do Sítio Histórico de Sobral-CE - Parente, José Reginaldo Feijão (2020)
The research focuses on the phenomenon of affects experienced in relation to cultural heritage in the context of the city of Sobral. The study of the theme gains relevance due to the recognition that in the transactional dynamics of residents of urban areas with cultural heritage, whether material or immaterial, it has social, political, economic, ethical and affective implications. Thus, the general objective is to understand the affects in the context of the cultural heritage of a medium-sized city in the interior of the state of Ceará. The work is structured in the form of articles and organized in 04 (four) studies. The first is characterized as a systematic review work in which 11 national articles that fit the purposes of the investigation were analyzed. The second study was characterized as a theoretical essay in which it reflected on the process of heritage development in Sobral considering 03 (three) historical landmarks with several consequences including the affective dimensions of the local population. The third study, on the other hand, comprised fieldwork in which 250 residents of Sobral were consulted regarding which heritage sites they considered most representative of the city and the meanings and affections in relation to them. Several were nominated, but three stood out: Arco de Nossa Senhora de Fátima, left bank of the Acaraú river and Becco do Cotovelo. The last study resorted to the application of the Affective Maps Generating Instrument with students from the State University Vale do Acaraú - UVA as members and former members of the Tutorial Education Program - PET pedagogy who participated in the urban trails project. Espinosa draws attention to sad and joyful passions. These are conditioned by the types of bonds established in the relationship of man with other bodies, which can produce potentializing or depotentializing affects. Vygostky, on the other hand, breaks with the mechanistic-based psychological tradition as well as the idealistbased tradition which separated reason-emotion, body-mind. Both Espinosa and Vigotski put affections in a new perspective, no longer as something undesirable that needed to be controlled or denied, but as a constituent element of human reality. The results of the indicated studies revealed that there is a growing interest in the subject of affections and cultural heritage, despite a very incipient movement; In the history of the investigated city, the heritage reflected not only the development, but the political-economic uses and its repercussions in the field of affections; The feelings and identifications with the spaces are related to the sociodemographic profile of the inhabitants; And finally, in the researched city, there was a predominance of esteem affections in a place of pleasantness, belonging and enhancing contrast.